A comparative physicochemical and pharmacological evaluation of dexamethasone sodium phosphate and betamethasone sodium phosphate mucoadhesive gels for the treatment of oral submucous fibrosis in rats - Vijaybhaskar Desai; Sidramappa Shirsand; Gurunath Surampalli (Universidade de São Paulo, 2022)
Abstract The present study is aimed to formulate steroidal oral mucoadhesive gels of dexamethasone sodium phosphate and betamethasone sodium phosphate. Six gel formulations each of dexamethasone sodium phosphate and betamethasone sodium phosphate prepared using two different polymers carboxymethyl cellulose sodium and hydroxypropyl methylcellulose, in variable proportions. All the formulations subjected for assessment of various physicochemical parameters and mechanical properties. The formulations BSP5 and DSP5, both containing 1.25 % carboxymethyl cellulose sodium, 1.25 % hydroxypropyl methylcellulose, exhibiting mucoadhesive strength of 12.300 ± 0.004 and 12.600 ± 0.01, adhesiveness of 28.04 ± 00 and 30.02 ± 00, cohesiveness of 28.04 ± 00 and 30.02 ± 00, drug release of 86.869 ± 0.380 % and 88.473 ± 0.457 % respectively were considered as promising ones and were further subjected for stability studies and in vivo study in male albino rats. Formulation DSP5 upon oral application for 4 months in arecoline induced oral submucous fibrosis rats, showed more than 80 % reduction in fibrosis as compared with BSP5 which showed nearly 50 % reduction. These results were concluded on the basis of histopathological profile and weight gain among the experimental animals during in vivo study. Hence, DSP5 by minimizing the painful injuries and morbidities justifies being suitable noninvasive model for OSMF treatment.